2020
DOI: 10.1186/s40069-019-0386-4
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Strengthening of RC Beams with Continuous Spiral Near-Surface Mounted Steel Wire Rope

Abstract: The strength of reinforced concrete members can be enhanced using externally bonded reinforcement (EBR) and near surface mounted (NSM) methods. However, small number of studies has adopted the NSM method for torsional strengthening. To date, no study has examined the use of spiral NSM steel wire rope and epoxy adhesives for torsional strengthening. Therefore, this study examines the behaviour of RC beams subjected to the combined actions of torsion and bending moment when they are strengthened with spiral NSM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
0
8
0
3
Order By: Relevance
“…Conventional shear reinforcement, which functions to withstand bending moment loads, is converted into spiral reinforcement installed continuously on the axis of the concrete block and acts as reinforcement to withstand shear forces. Research related to spiral reinforcement is described by Ibrahim et al [21], Askandar and Mahmood [22], Ibrahim et al [23], and Al-Faqra et al [24]. The change of vertical shear reinforcement into spiral shear reinforcement in beams is considered to increase the flexural capacity; according to Shatarat et al [25], the shear capacity of SCC beams reinforced with rectangular spiral reinforcement is higher than traditional shear reinforcement regardless of the distance and angle of inclination for the stirrups.…”
Section: Figure 1 Compression-tension Of a Flexural Beam Figure 2 Rec...mentioning
confidence: 99%
“…Conventional shear reinforcement, which functions to withstand bending moment loads, is converted into spiral reinforcement installed continuously on the axis of the concrete block and acts as reinforcement to withstand shear forces. Research related to spiral reinforcement is described by Ibrahim et al [21], Askandar and Mahmood [22], Ibrahim et al [23], and Al-Faqra et al [24]. The change of vertical shear reinforcement into spiral shear reinforcement in beams is considered to increase the flexural capacity; according to Shatarat et al [25], the shear capacity of SCC beams reinforced with rectangular spiral reinforcement is higher than traditional shear reinforcement regardless of the distance and angle of inclination for the stirrups.…”
Section: Figure 1 Compression-tension Of a Flexural Beam Figure 2 Rec...mentioning
confidence: 99%
“…Sometimes, the reinforced concrete structures are exposed to torsional moments, and the strength for torsion needs to be increased. Therefore, the ways for these member strengthening in torsion are necessary [2,3,4], to strengthen concrete (RC) structures, the strengthening materials can be applied in two main different manners: (1) externally bonded reinforcement (EBR), in which the strengthening materials are adapted externally to the concrete surface; and (2) near surface mounted (NSM), in which the strengthening materials are integrated into the concrete surface in pre-cut grooves (Askandar, N.H. and Mahmood, A.D.,2020) [5].…”
Section: Introductionmentioning
confidence: 99%
“…(Askandar, N.H. and Mahmood, A.D., 2020) [5] investigate the properties of RC beams subjected to the combined actions of torsion and bending moment when strengthened by spiral NSM steel wire rope in various configurations. The experimental study included cast and investigated six rectangular RC beams, one of these beams is considered as a control beam (without strengthening), while the others were reinforced with spiral NSM steel wire rope with a 45° spiral inclination.…”
Section: Introductionmentioning
confidence: 99%
“…It enhances the shear capacity and reduces the construction cost [10]. Thus, it is found that few researchers use spiral stirrups rather than traditional vertical stirrups [11]. Since the shear failure mechanism is complex, the experimental test of beams underestimated the contribution of the stirrups but increased the contribution of the concrete component.…”
Section: Introductionmentioning
confidence: 99%